STUDI PENERAPAN MEDIA KUIS INTERAKTIF QUIZIZZ TERHADAP HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN MATEMATIKA - Suvriadi Panggabean; Tua Halomoan Harahap (MES: Journal of Mathematics Education and Science, 2020)
The purpose of this study was to see the contribution of interactive quiz media Quiziz media to improving student learning outcomes of Mathematics Education study program. The research used was quasi-experimental with a research sample of students of the mathematics education study program at the Faculty of Teacher Training and Education, Muhammadiyah University of North Sumatra, class of 2017. The techniques and data used were questionnaire and test methods. The results of the calculation using the t-test obtained that the value of tcount is 2.134 and when compared with the value of ttable is 2.004, obtained tcount ttable. The data shows that the student learning outcomes in the geometry transformation subject using interactive quiz media are better than those without using media. Media quizzes with quizizz significantly contribute to student learning outcomes, which is around 78%The purpose of this study was to see the contribution of interactive quiz media Quiziz media to improving student learning outcomes of Mathematics Education study program. The research used was quasi-experimental with a research sample of students of the mathematics education study program at the Faculty of Teacher Training and Education, Muhammadiyah University of North Sumatra, class of 2017. The techniques and data used were questionnaire and test methods. The results of the calculation using the t-test obtained that the value of tcount is 2.134 and when compared with the value of ttable is 2.004, obtained tcount ttable. The data shows that the student learning outcomes in the geometry transformation subject using interactive quiz media are better than those without using media. Media quizzes with quizizz significantly contribute to student learning outcomes, which is around 78%